RANCANG BANGUN TANGAN PROSTHESIS MENGGUNAKAN FLEX SENSOR DAN MODUL BLUETOOTH BERBASIS ARDUINO - Alpin Kurnia Putra (JIMSTEK: Jurnal Ilmiah Sains dan Teknologi, 2020)
One medical procedure taken to save a patient's life is amputation. The real consequence of amputation for patients is loss of limb function. Prosthesis is an artificial device that replaces body parts, usually in the form of hands, feet, and even organs in humans. This research aims to make a prosthetic hand to support the function of the lost arm in an amputee or a person with a disability under the elbow on condition that the person still has another hand that is still intact. This prosthesis hand works is with the concept of mirroring, which is when the patient's whole finger is moved, then the same finger on the prosthesis hand will also move. This research used trial and error methods. This prosthesis design used the Brunel Hand 2.0 model as prosthesis references. The concept of mirroring is applied by attaching the flex sensor to the patient's hand that is still intact, so that the values which read can be processed into movement on the fingers of the prosthesis. In this research, the prosthesis hand made has the disadvantage of less strong grip due to servo motor torque absorbed by the flexibility of the nylon rope, reading the value of the flex sensor that is too volatile and fast causing the servo motor to become noisy and wasteful of power, and the installation of the servo motor entirely in the body resulting in space to install the prosthesis hand becomes narrow.